Pengaruh Perputaran Piutang, Resiko Bisnis, dan Likuiditas terhadap Profitabilitas Perusahaan Era Pancemi Covid-19: Studi pada Perusahaan Sub Sdektor Perkebunan & Tanaman Pangan Periode 2019-2021 - Elva Syanistya Nur Khasanah; Gendro Wiyono; Risal Rinofah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the impact of covid 19 as seen from Accounts Receivable Turnover, Degree Of Operating Leverage (DOL), Current Ratio (CR) to Return On Investment (ROI) in plantation & food crop sub-sector companies listed on the IDX during the 2019-2021 period.The population of this study is the plantation & food crop sub-sector companies for the period 2019-2021. In this study, accounts receivable turnover, DOL, and CR became the independent variables, while ROI became the research variable. The results of the partian test (t test) show that the accounts receivable turnover and current ratio variables have no significant effect on ROI while the DOL variable has a significant effect on ROI because the sign value is 0.00 < 0.005 and t-count 8.920 > t-table 2.00100 thus the DOL has an influence on ROI Keyword : Receivable Turnover, Degree Of Operating Leverage (DOL), Current Ratio (CR), Return On Investment (ROI)